The Variation of the Black Image in Hei Nu Yu Tian Lu from the Skopos Theory - Jiaying, Guo (International Journal of Linguistics, Literature and Translation, 2021)
Lin Shu, who does not comprehend English, translated roughly 170 foreign novels. His second translation Hei Nu Yu Tian Lu (Uncle Tom’s Cabin), has influenced Chinese translation history and modern writers. Many Chinese Scholars has studied Hei Nu Yu Tian Lu before, but no works are studying the variation of the black image in Hei Nu Yu Tian Lu. This paper explains how the black image varies from the black slave to the Chinese literary slave after translation based on skopos theory.